2005
DOI: 10.1261/rna.2550105
|View full text |Cite
|
Sign up to set email alerts
|

The pseudouridine synthase RluD is required for normal ribosome assembly and function in Escherichia coli

Abstract: RluD is the pseudouridine synthase responsible for the formation of C1911, C1915, and C1917 in Escherichia coli 23S rRNA. Previous work from our laboratory demonstrated that disruption of the rluD gene and/or loss of the pseudouridine residues for which it is responsible resulted in a severe growth phenotype. In the current work we have examined further the effect of the loss of the RluD protein and its product pseudouridine residues in a deletion strain lacking the rluD gene. This strain exhibits defects in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 37 publications
6
94
0
Order By: Relevance
“…However, site-directed mutagenesis of several well-conserved amino acids of Maa2 (including the active site Asp) revealed that isomerization activity is not required for trans splicing, but splicing requires the physical presence of the protein (Perron et al, 1999). Similar results were reported for E. coli TruB and RluD pseudouridine synthase mutants (Gutgsell et al, 2000(Gutgsell et al, , 2001(Gutgsell et al, , 2005 as well as for yeast rRNA pseudouridine synthase Cbf5p (Lafontaine et al, 1998). By analogy to Maa2, it is thus possible that the reductions in translation that we observed in svr1 plants might be due to a defect in splicing of a chloroplast mRNA for a protein required for chloroplast ribosome assembly/function.…”
Section: Possible Role Of Svr1 In Chloroplast Rna Metabolismsupporting
confidence: 67%
“…However, site-directed mutagenesis of several well-conserved amino acids of Maa2 (including the active site Asp) revealed that isomerization activity is not required for trans splicing, but splicing requires the physical presence of the protein (Perron et al, 1999). Similar results were reported for E. coli TruB and RluD pseudouridine synthase mutants (Gutgsell et al, 2000(Gutgsell et al, , 2001(Gutgsell et al, , 2005 as well as for yeast rRNA pseudouridine synthase Cbf5p (Lafontaine et al, 1998). By analogy to Maa2, it is thus possible that the reductions in translation that we observed in svr1 plants might be due to a defect in splicing of a chloroplast mRNA for a protein required for chloroplast ribosome assembly/function.…”
Section: Possible Role Of Svr1 In Chloroplast Rna Metabolismsupporting
confidence: 67%
“…Deletion of helix H69 results in a dominant lethal phenotype and hampers subunit association in the absence of tRNA, even at magnesium ion concentrations as high as 20 mM 33 . Chemical modifications of specific nucleotides in H69 also hinder 70S ribosome formation 34,35 . Cryo-EM studies of an RRF/70S ribosome binary complex suggest that RRF Domain II is also in close proximity to 16S rRNA helix h44 and ribosomal protein S12 in the 30S subunit 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Saccharomyces cerevisiae have suggested that nearly 200 proteins function as ribosome assembly factors (Venema and Tollervey 1999;Harnpicharnchai et al 2001;Grandi et al 2002;Saveanu et al 2003). In contrast, only 10-15 assembly factors have been identified in E. coli (Alix and Guerin 1993;Bylund et al 1998;El Hage et al 2001;Charollais et al 2003Charollais et al , 2004Inoue et al 2003;Gutgsell et al 2005;Bharat et al 2006;Hwang and Inouye 2006;Jiang et al 2006), suggesting either a lower degree of ribosomal complexity in prokaryotes, or that additional ribosome assembly factors remain to be discovered (FromontRacine et al 2003;Hage and Tollervey 2004).…”
Section: Introductionmentioning
confidence: 99%